Mechanical properties and behaviour of concrete reinforced with spiral-shaped steel fibres under dynamic splitting tension - Hao, Y.; Hao, Hong (2016)
Concrete exhibits excellent resistance to compressive forces, but is brittle and weak in tension. Various types of fibres have been investigated by many researchers to improve the ductility and energy absorption capability of concrete materials and structures under static and blast and impact loadings. Spiral-shaped steel fibres were recently proposed as reinforcement in a concrete matrix and it was found that spiral fibre reinforcement can significantly improve the ductility, crack control ability and energy absorption capacity of concrete material under static and impact compressive loads. This paper presents an experimental study of the static and dynamic properties of steel fibre reinforced concrete (SFRC) materials under splitting tension. SFRC materials mixed with spiral-shaped steel fibres of different volume fractions were prepared and tested. A high-speed camera was used to capture the deformation, failure and crack opening process of the tested specimens. The contribution of spiral fibres to the mechanical properties and behaviour of concrete at high strain rate under splitting tension was investigated. Analyses of the test results revealed the effectiveness of spiral fibres in improving the performance of SFRC (e.g. crack control, energy absorption capability and more pronounced rate sensitivity under dynamic splitting loading). Moreover, crack opening and closing (pull-back by spiral fibres) processes were observed, demonstrating the excellent bonding and outstanding performance of spiral steel fibres in maintaining the integrity of the concrete material, thus resulting in significant improvements in impact resistance and energy dissipation.